2021
DOI: 10.1002/smi.3075
|View full text |Cite
|
Sign up to set email alerts
|

Latent profiles of emotion regulation strategies associated with alexithymia, nonsuicidal self‐injury and resilience among nursing students

Abstract: The present study sought to better understand the complex nature of emotion regulation in nursing students by exploring patterns of emotion regulation strategies (ERSs), and to examine the relationships between these unique profiles with alexithymia, nonsuicidal self‐injury (NSSI) and resilience. A total of 1960 nursing students (Mage = 19.56, SD = 1.13 years) were recruited. Using latent profile analysis, nursing students were classified into four profiles based on their ERS use: high reaction profile (HRP; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Among a sample in Indonesia, a positive correlation was found between difficulties in emotional regulation as measured by the Difficulties in Emotion Regulation Scale (Gratz & Roemer, 2004) and self‐injury (Safira et al., 2022). The contribution of specific emotion regulation strategies was explored in China using latent profile analyses (Mao et al., 2021). Students categorized as having high (using a range of positive and negative emotion regulation strategies) and medium (average emotion regulation engagement) emotional regulation profiles had higher incidence of self‐injury and alexithymia than students with low (rarely engaging in emotional regulation strategies), or adaptive reaction profiles (engaging in planning and positive reappraisal instead of rumination, catastrophizing and blaming others) (Mao et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among a sample in Indonesia, a positive correlation was found between difficulties in emotional regulation as measured by the Difficulties in Emotion Regulation Scale (Gratz & Roemer, 2004) and self‐injury (Safira et al., 2022). The contribution of specific emotion regulation strategies was explored in China using latent profile analyses (Mao et al., 2021). Students categorized as having high (using a range of positive and negative emotion regulation strategies) and medium (average emotion regulation engagement) emotional regulation profiles had higher incidence of self‐injury and alexithymia than students with low (rarely engaging in emotional regulation strategies), or adaptive reaction profiles (engaging in planning and positive reappraisal instead of rumination, catastrophizing and blaming others) (Mao et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of specific emotion regulation strategies was explored in China using latent profile analyses (Mao et al., 2021). Students categorized as having high (using a range of positive and negative emotion regulation strategies) and medium (average emotion regulation engagement) emotional regulation profiles had higher incidence of self‐injury and alexithymia than students with low (rarely engaging in emotional regulation strategies), or adaptive reaction profiles (engaging in planning and positive reappraisal instead of rumination, catastrophizing and blaming others) (Mao et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, nursing students with higher psychological resilience tend to adopt positive ways to cope with stress and demonstrate better clinical adaptability ( Amsrud et al, 2019 ; Li and Hasson, 2020 ). Mao et al (2022) found that psychological resilience plays a positive role in arousing positive emotions. In addition, Liu et al’s (2021) research found that psychological resilience is a protective factor and positively correlates with emotional regulation ability.…”
Section: Introductionmentioning
confidence: 99%